ANALISIS KESALAHAN SISWA DALAM PEMECAHAN MASALAH BERDASARKAN PENDAPAT JOHN W. SANTROCK PADA POKOK BAHASAN BANGUN RUANG SISI LENGKUNG DITINJAU DARI GAYA BELAJAR DAN GAYA BERPIKIR SISWA - Rosyida, Entyka Mayhasti; Riyadi, Riyadi; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2016)
Abstract: This research aimed to find out the errors and causes of studentsâ with learning and thinking styles in non-polyhedra geometry. The subject of research was 30 students in SMP Negeri 1 Plantungan, in the school year of 2012/2013. The selection of research subjects is based on the problems arising from students in mathematical problem solving, especially in non-polyhedra geometry. Data triangulation used in this research was method triangulation. Before questionnaire was distributed, the author had conducted observation. After in non-polyhedra geometry was taught, diagnostic test item were administered and the result with most errors were selected as the research subject. The result of research are Auditory-Sequential students includes determining a formula error, errors of count, and the error determining unit. The causes were the students donât understanding the concept of matter; Auditory-Random students errors included that of not writing all the elements on the part and the error of count. The causes were the students less creativity in choosing the measure of problem solving; Visual-Sequential students involved errors set the formula, an error entering element values into the formula, and errors of calculating. The causes were students not understanding concept of matter; Visual-Random student errors included that of determining the formula, converting volume unit, and of drawing a conclusion from the result of calculation. The causes were students paying attention imprecisely to answer and question; Kinesthetic-Sequential students involved errors set the formula, an error including the value element into formula, calculating error, and the error determining unit. The causes were students not forgetting the formula of objects, working in the problem imprecisely, and working the problem in hurry; Kinesthetic-Random students involved errors identifying any elements known from the picture, set the formula errors, errors of counting, and error of determining unit. The causes were that the students identified picture imprecisely.Key words: error analysis, problem solving, learning style, thinking style.